Effect of Kyphoplasty on Pain Control and Vertebral Restoration - Kilinc, Mustafa C.; Alpergin, Baran C.; Ozpiskin, Omer M.; Aktan, Eray S.; Dogan, Ihsan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Background and Aim Numerous studies have been conducted regarding vertebral restoration, development of kyphotic deformity, and pain control following balloon kyphoplasty. However, there is no consensus regarding the ideal time to perform kyphoplasty. Herein, we aimed to compare the results of treatment of different vertebral levels following early or late kyphoplasty.Patients and Methods Between 2017 and 2022, 283 patients with single-level osteoporotic vertebral fractures were retrospectively reviewed. Patients in whom visual analog scale (VAS) values were recorded, and osteoporosis tests performed were included in the study. Traumatic single-level fractures in patients with osteoporosis who were aged > 60 years were included. Patients with a history of malignancy, previous spinal surgery, or neurological deficits were excluded. A total of 100 patients met the inclusion criteria. A total of 50 patients underwent kyphoplasty within 3 days of sustaining the fracture (Group 1), and 50 patients underwent kyphoplasty more than 3 days after sustaining the fracture (Group 2). Groups A, B, and C included fractures at the T7–T11 levels, T12–L1 levels (thoracolumbar junction), and L2–L5 levels, respectively. These groups were compared among themselves. Bilateral balloon kyphoplasty was performed under sedation in the prone position. Preoperative and postoperative VAS scores, anterior vertebral heights, and kyphotic angles (KAs) were measured and recorded. The vertebral segments that underwent early and late kyphoplasty were also compared among themselves.Results In all the patients who underwent early or late kyphoplasty, there was a significant decrease in the KA and a significant increase in vertebral heights during the early postoperative period (p < 0.001). There was no significant change in the vertebral heights and KA between the early and late postoperative periods (p = 0.780). Early kyphoplasty demonstrated better pain control with a greater improvement in VAS score (p < 0.001) than late kyphoplasty.Conclusion Kyphoplasty plays an important role in reducing pain and ensuring early mobilization in older patients. In our study, the improvements in both symptoms and radiological features are concrete evidence in favor of performing early kyphoplasty.
Keywords: early mobilization; kyphotic deformity; prone position; vertebral restoration